2019
DOI: 10.1371/journal.pone.0213382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and risk-factor analysis of the Ponseti Method in a low-resource setting: Clubfoot care in Haiti

Abstract: PurposeThe Ponseti Method has dramatically altered the management of clubfoot, with particular implications for limited-resource settings. We sought to describe outcomes of care and risk factors for sub-optimal results using the Ponseti Method in Haiti.MethodsWe conducted a records review of patients presenting from 2011–2015 to a CURE Clubfoot clinic in Port-au-Prince, Haiti. We report patient characteristics (demographics and clinical), treatment patterns (cast number/duration and tenotomy rates), and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…Gelfer et al by conducting a systematic review of 10535 clubfeet found that the relapse rate reported in various studies was between 1.9% and 45%, which increased over follow-up time [32]. A study by Qudsi et al, which examined clinical outcomes and risk factors for the Ponseti method in 168 children with clubfoot, found that female gender and a higher Pirani score increased the risk of recurrence [33].…”
Section: Discussionmentioning
confidence: 99%
“…Gelfer et al by conducting a systematic review of 10535 clubfeet found that the relapse rate reported in various studies was between 1.9% and 45%, which increased over follow-up time [32]. A study by Qudsi et al, which examined clinical outcomes and risk factors for the Ponseti method in 168 children with clubfoot, found that female gender and a higher Pirani score increased the risk of recurrence [33].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the literature. 1 , 5 , 8 , 10 , 15 , 20 , 24 , 30 , 34 , 37 , 38 The main cause of the first recurrence was the non-adherence and non-compliance to the retention programme in 98.7% of the recurrent cases, while it was idiopathic in 1.3%, with no obvious cause for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 15 , 19 Besides, there is no consensus on the minimal number of hours of use of the FAB per day to prevent recurrence. 9 , 27 , 30 , 31 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Nonphysician providers thus could provide a supplemental and novel role in task sharing clubfoot care, and their involvement could facilitate both treatment and prevention of recurrence. Moreover, as patient education was routinely listed as one of the main barriers to successful treatment, Ponseti-trained nonphysician personnel could facilitate the spread of the Ponseti method and expand access to treatment by educating and empowering patients and their caregivers to receive optimal care (5, 7, 8). In short, sharing the task of providing caregiver education may alleviate the burden disproportionally placed on a scarce supply of orthopedic surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…While the Ponseti method has quickly become the mainstay of clubfoot treatment in most parts of the world – US, UK, Australia, India, and parts of Africa – its dissemination and successful implementation in Latin America has been slower (4). Despite clubfoot being reported as one of the most commonly encountered pediatric orthopedic conditions in parts of Latin America, when compared with patients in higher income nations, patients have a later age of presentation, more time spent in the manipulation and casting phase, lower rates of tenotomy, and higher rates of relapse (5, 6). Inefficient healthcare systems may be partly responsible for this inequity and shortage of trained orthopedic surgeons additionally contributes to barriers to care (4, 7–9).…”
Section: Introductionmentioning
confidence: 99%